2019
DOI: 10.1039/c8na00301g
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale mechanical control of surface electrical properties of manganite films with magnetic nanoparticles

Abstract: Mechanical control of electrical properties in complex heterostructures, consisting of magnetic FeOx nanoparticles on top of manganite films, is achieved using atomic force microscope (AFM) based methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In addition, the local compression by the C-AFM tip induces a local flexoelectric effect, modifying the oxygen and electron concentrations in the film. 30 This flexoelectric effect is also combined with a compositional Vegard strain originating from the difference of the electron and ion distribution due to the lattice dilatation (when the concentration of oxygen vacancy 31 is increased, the unit cell volume is also increased, modifying the local electronic properties of the material) as modeled in Ref. 29.…”
Section: Figures 3a and 3bmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the local compression by the C-AFM tip induces a local flexoelectric effect, modifying the oxygen and electron concentrations in the film. 30 This flexoelectric effect is also combined with a compositional Vegard strain originating from the difference of the electron and ion distribution due to the lattice dilatation (when the concentration of oxygen vacancy 31 is increased, the unit cell volume is also increased, modifying the local electronic properties of the material) as modeled in Ref. 29.…”
Section: Figures 3a and 3bmentioning
confidence: 99%
“…It was observed that this conductance switching persists for a long time (hours) due to the slow relaxation process of oxygen vacancies. 30 Related to these mechanisms, we consider three cases. i) The presence of the SAM between the LSMO surface and the C-AFM tip reduces both the applied electric field -and the current passing -through the LSMO film.…”
Section: Figures 3a and 3bmentioning
confidence: 99%